All that you leave behind : a memoir - Carr, Erin Lee (Ballantine Books, 2019)
"A celebrated journalist, bestselling author, and recovering addict, David Carr was in the prime of his career when he collapsed in the newsroom of The New York Times in 2015. Shattered by his death, his daughter Erin Lee Carr, an up-and-coming documentary filmmaker at age twenty-seven, began combing through the entirety of their shared correspondence--1,936 items in total. What started as an exercise in grief quickly grew into an active investigation: Did her father's writings contain the answers to the questions of how to move forward in life and work without your biggest champion by your side? How could she fill the space left behind by a man who had come to embody journalistic integrity, rigor, and hard reporting, whose mentorship meant everything not just to her, but to the many who served alongside him? In All That You Leave Behind, David Carr's legacy is a lens through which Erin comes to understand her own workplace missteps, existential crises, relationship fails, and toxic relationship with alcohol. Featuring photographs and emails from the author's personal collection, this coming-of-age memoir unpacks the complex relationship between a daughter and her father, their mutual addictions and challenges with sobriety, and the powerful sense of work and family that comes to define them"--